2020
DOI: 10.1099/jmm.0.001226
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of heavy metal-induced antibiotic resistance by dandelion root extracts and taraxasterol

Abstract: Introduction. Metal exposure is an important factor for inducing antibiotic resistance in bacteria. Dandelion extracts have been used for centuries in traditional Chinese and Native American medicine. Aim. We assessed the effects of dandelion water extracts and taraxasterol on heavy metal-induced antibiotic resistance in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Another study suggested the use of dandelion root extracts and taraxasterol for the reversal of metal (Cd, Ni, As) induced ampicillin and kanamycin resistance in E. coli cells (Yang and Zhang, 2020). While treatment of E. coli cells with low concentrations of Dandelion root extract alone did not seem to show any antimicrobial activity, the addition of kanamycin and ampicillin along with the heavy metals and the root extracts significantly reduced the bacterial growth, indicating that dandelion root extracts can be effective modulators against metal‐induced antibiotic resistance.…”
Section: Strategies To Disarm the Co‐selection Of Heavy Metal And Ant...mentioning
confidence: 99%
“…Another study suggested the use of dandelion root extracts and taraxasterol for the reversal of metal (Cd, Ni, As) induced ampicillin and kanamycin resistance in E. coli cells (Yang and Zhang, 2020). While treatment of E. coli cells with low concentrations of Dandelion root extract alone did not seem to show any antimicrobial activity, the addition of kanamycin and ampicillin along with the heavy metals and the root extracts significantly reduced the bacterial growth, indicating that dandelion root extracts can be effective modulators against metal‐induced antibiotic resistance.…”
Section: Strategies To Disarm the Co‐selection Of Heavy Metal And Ant...mentioning
confidence: 99%
“…In addition to the illustrated active ingredients above, the whole dandelion herb harbors amaroid, resin, synanthrin, pectin and etc [35,36] . β-sitosterol, stigmasterol, linoleic acid were identified in dandelion root, and xanthophyll, phylloquinone, γ-aminobutyric acid, sulfonyl amino acids, ornithine acid in dandelion leaf, and capretin, sarcochediol, lutein in dandelion blossom, and β-sitosterol, folate in pollen [28,29,37] . A total of 66 trace elements have been detected in dandelion and among those Cd, Cu, Zn, Fe, Mn and Mo essential trace elements are higher in contents [38] (Chinese paper with DOI: 10.3969/ j. issn.1006-0111.2002.04.026).…”
Section: Active Ingredient In Dandelionmentioning
confidence: 99%
“…In recent years, traditional Chinese medicine (TCM) has been found to alleviate or even diminish bacterial resistance to antibiotics, which provides researchers with a new strategy for solving the serious problem of increased antibiotic resistance commonly seen in clinical practice [13,14]. Berberine is an isoquinoline alkaloid with extensive biological activity; it is extracted from a variety of plant taxa such as Berberis sargentiana Schneid, Coptis chinensis, and Philodendron.…”
Section: Introductionmentioning
confidence: 99%